2010
DOI: 10.1017/s0376892910000378
|View full text |Cite
|
Sign up to set email alerts
|

Patterning the distribution of threatened crayfish and their exotic analogues using self-organizing maps

Abstract: International audienceAbility to demonstrate statistical patterns of distribution by threatened species and by their potential competitors will determine success in forecasting locations at greatest risk, and ability to target management efforts. A self organizing map algorithm (SOM) was used to derive probabilities of presence of native (Austropotamobius pallipes) and exotic (Orconectes limosus, Pacifastacus leniusculus and Procambarus clarkii) crayfish species with respect to physical and landcover variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 51 publications
0
7
1
Order By: Relevance
“…This proportion is low given the fact that P. clarkii has invaded all sectors of Brière marshes and that ponds are close to these marshes in the study window. Several studies found larger colonization rates of waterbodies by P. clarkii: 22 to 51% in temporary ponds, 54% in permanent ponds, 32 to 84% in streams (Kerby et al, 2005;Cruz and Rebelo, 2007;Kopp et al, 2010) and a more rapid colonization process (Cruz and Rebelo, 2007). The low capture rate found in the present study can be explained with three non-mutually exclusive scenarios.…”
Section: > a Weak Colonization Of Ponds By P Clarkiicontrasting
confidence: 46%
See 1 more Smart Citation
“…This proportion is low given the fact that P. clarkii has invaded all sectors of Brière marshes and that ponds are close to these marshes in the study window. Several studies found larger colonization rates of waterbodies by P. clarkii: 22 to 51% in temporary ponds, 54% in permanent ponds, 32 to 84% in streams (Kerby et al, 2005;Cruz and Rebelo, 2007;Kopp et al, 2010) and a more rapid colonization process (Cruz and Rebelo, 2007). The low capture rate found in the present study can be explained with three non-mutually exclusive scenarios.…”
Section: > a Weak Colonization Of Ponds By P Clarkiicontrasting
confidence: 46%
“…But no study on the spatial distribution of this non-native species has been conducted to date on the network of ponds. Thus, to conserve the current biodiversity and functioning of these small waterbodies, which may strongly contribute to regional freshwater biodiversity, the distribution of P. clarkii should be mapped as Kerby et al (2005) and Kopp et al (2010) recommended. Indeed, invasion specialists highlighted that dispersal is very important for the success of an invasive species (Davis, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Chucholl (2016) found P. leniusculus to be the highest threat to indigenous crayfish species among six non-indigenous crayfish species in southwestern Germany. This translates, for instance, into P. leniusculus being a direct competitor for resources and shelter (Collas, Julien & Monnier, 2007;Dunn et al, 2009;Kopp et al, 2010). Besides, P. leniusculus is known to have a wider thermal tolerance than A. pallipes (Firkins & Holdich, 1993), and to display morphologically and physiologically advantageous traits, such as greater body size or fecundity allowing dominance over A. pallipes individuals (Holdich et al, 2009;Lowery & Holdich, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Ghia et al (2013) modelled the environmental niche of the A. pallipes complex in Northern and Central Italy and according to their study, increases in the temperature of the warmest quarter seemed critical for the risk of local extinctions. Also, in south-western France, Kopp et al (2010) used self-organising maps to correlate species probabilities of presence with land cover and physical variables, and found A. pallipes distribution to be restricted to headwaters with preference for forested areas and steep slope and P. leniusculus to occur at lower air temperatures. Also, in south-western France, Kopp et al (2010) used self-organising maps to correlate species probabilities of presence with land cover and physical variables, and found A. pallipes distribution to be restricted to headwaters with preference for forested areas and steep slope and P. leniusculus to occur at lower air temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SOM has been widely used in the global oceanographic community (Liu et al, 2006;Liu and Weisberg, 2011). It has been successfully applied to a variety of problems in which a reduction of dimensionality (Murtagh and Hernandez Pajares, 1995), extraction of patterns (Kopp et al, 2010) or detecting outliers (Munoz and Murazabal, 1998) was performed. Although the method prefers large datasets, which are provided via remote sensing techniques (e.g., satellites, Richardson et al, 2003) or climate studies (e.g., Morioka et al, 2010), SOM has been successfully applied to limited datasets, such as in situ oceanographic data, from which patterns have been extracted and connected to driving processes and forces (e.g., Fendereski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%